Marilyn Renfree interviewed by Ragbir Bhathal for the Australian women scientists oral history project - Renfree, Marilyn B.; Bhathal, Ragbir (Ragbir Singh) (1998)
Professor Marilyn Renfree, an academic and zoologist, talks about her family background; interest in science; schooling at Queanbeyan Public School and Canberra Church of England Girls Grammar School; undergraduate degree at Australian National University with a major in biological sciences and PhD on embryonic diapores. She then discusses postdoctoral studies and their importance; work at Murdoch University on marsupial reproduction; move to Monash University in 1982; plans for Zoology Dept. at University of Melbourne; reasons for interest in marsupials and monotremes and problems of conservation. Renfree then talks about the publication she did with Hugh Tyndale-Biscoe on the reproductive physiology of marsupials; women in science and her career achievements.
Recorded on May 15, 1998 in Melbourne.
Digital master available
Timed summary and uncorrected transcript (typescript, 24 leaves) available.
Keywords: Renfree, Marilyn B. -- Interviews; Zoologists -- Australia -- Interviews; Scientists -- Australia -- Interviews; Scientists; Zoologists; Academics